약액처리장치 및 그 유량제어방법 (1999)
공급되는 처리액량과 대략 동량의 처리액을 처리조(處理槽)로부터 배출하여, 처리조내의 처리액의 양을 일정하게 유지하려고 하면, 처리조내의 처리액의 흐름이 흐트러져 층류(層流)로 유지하는 것이 곤란하였다. 처리조(2)(본조(3))의 조(槽)외로부터 처리액(21)이 공급되는 동시에, 이 처리조(2)(본조(3))의 하부로부터 처리액(21)이 배출되는 다운플로방식의 약액(藥液)처리장치(1)로서, 본조(3)의 처리액배출측에, 본조(3)내의 처리액(21)의 흐름을 대략 층류상태로 유지한 상태에서 처리액(21)을 본조(3)외로 배출시키는 회전식 펌프로 이루어지는 펌프(5)가 구비되어 있는 것이다. When trying to keep the amount of a liquid treating chemical in a treating bath constant by discharging almost the same amount of the liquid treating chemical as the liquid treating chemical supplied, the flow of the liquid treating chemical in the treating bath fell into disorder, which made it hard to keep the flow of the liquid treating chemical in the treating bath in the laminar state.A down-flow type chemical treating apparatus 1 in which a liquid treating chemical 21 is supplied from the outside of a treating bath 2 (main bath 3) while the liquid treating chemical 21 is discharged from the bottom portion of the treating bath 2 (main bath 3), comprising a pump 5 on the chemical discharging side of the main bath 3 which consists of a rotary pump allowing to discharge the liquid treating chemical 21 to the outside of the main bath 3 keeping the flow of the liquid treating chemical 21 substantially in the main bath 3 almost in the laminar state.